Development of wearable pulse oximetry for telehealth monitoring system - Khalifa, Othman Omran; Khan, T. A.; H. M. , Hazzaa (Politechnica Publishing House, 2014)

(untitled)
In today’s healthcare practice there has been increasing interest in wearable/mobile health monitoring devices. These devices allow continuous or intermittent monitoring of physiological signals for the diagnosis as well as treatment of diseases. One of these devices is Pulse oximeter which indirectly measures the oxygen saturation of a patient's blood (as opposed to measuring oxygen saturation directly through a blood sample) and changes in blood volume in the skin, producing a photoplethysmograph (PPG). the main goal of this paper is to demonstrate overall the process involved in the development of a cost-effective user-friendly Pulase Oximetry for Telehealth monitoring system.